41. WebCT: a major shift of emphasis - Morningstar, Barbara; Schubert, Jeremy; Thibeault, Kristine (International Review of Research in Open and Distributed Learning, 2004)
The evaluation reports in this series usually feature several products at once. The current review, however, comes at a time when one of the most widely used (and expensive) online learning management systems is undergoing a major change in its marketing strategy and corporate focus. WebCT is currently evolving to a new version (WebCT Vista), with much attendant discussion by distance education (DE) users. The current review, as the others in this series, adds the DE student's perspective to this discussion. The review compares the existing WebCT Campus Edition with the new WebCT Vista, and examines some of the problems associated with the migration to Vista at the institutional level. A response to the report by the WebCT company is appended.